Efforts to Increase Student Motivation Through Peer Tutor Group Guidance in Class X IPS 1: Upaya Meningkatan Motivasi Belajar Siswa Melalui Bimbingan Kelompok Tutor Sebaya Pada Kelas X IPS 1 - Rosman Kurnia (Journal of Vocational Education and Information Technology (JVEIT), 2021)
This study investigates  problem of learning anxiety experienced by students and shows that. This is very important because developmental task that adolescent students must have is Emotional independence which will support him / her to develop their personality, complete study assignments and plan future careers. Most of  students in guidance class did not understand how to deal with learning anxiety problems. Research method chosen was classroom action research (PTK) whose activities were based on  cycle consisting of planning, implementing actions, observing and reflecting. Development of cycle depends on the reflection that is done in each cycle. Tools used were observation guidelines and reflection notes for each cycle. Way to draw conclusions  to process the data quantitatively and describe results qualitatively. The findings in the study were: 1) level of student anxiety showed that  behavioral group counseling showed a decrease in the level of student anxiety seen from an average value of 18 or 51.43% to 3 (8.75%) which indicated a significant reduction in anxiety problems. , 2) seen that student's activeness shows an increase in percentage from 34.29% in first cycle to 85.71% in second cycle, which means that with behavioral counseling all students can be actively involved in activities aimed at alleviating anxiety problems they experience. Conclusion is that behavioral group counseling can reduce student learning anxiety, which changes students' understanding of importance of reducing anxiety in learning. So, authors suggest that behavioral group coaching can be applied not only to coaching activities, but also learning activities in general.